MICROSTRUCTURAL AND FUNCTIONAL ABNORMALITIES IN THE BRAIN OF PATIENTS WITH TEMPORAL LOBE EPILEPSY AS REVEALED WITH MR IMAGING - E. M. Perepelova; V. A. Perepelov; M. S. Merkulova (Эпилепсия и пароксизмальные состояния)
Diagnosis of epilepsy remains a challenging task facing physicians of various specialties. When epilepsy is suspected, neuroimaging is one of the major diagnostic tests able to localize the epileptic site and identify the underlying pathology; this information is indispensable in making the diagnosis and predicting the prognosis of the disease. Magnetic resonance imaging (MRI) is the most common modality widely used due to its high sensitivity and specificity in detecting of subtle abnormalities in the brain structure. In addition to the structural pulse sequences, the epilepsy-specific MRIprotocol incorporates a number of recently introduced techniques for the assessment of local functional abnormalities. In this report, the epilepsy-specific protocol that includes the updated pulse sequences technique was used in patients suspected of having temporal lobe epilepsy. Using this technique, characteristic changes in the structure and function of local brain segments in temporal epilepsy were demonstrated.